Brief Report: Human Pluripotent Stem Cell Models of Fanconi Anemia Deficiency Reveal an Important Role for Fanconi Anemia Proteins in Cellular Reprogramming and Survival of Hematopoietic Progenitors123. (24th April 2013) - Yung, Sun K.; Tilgner, Katarzyna; Ledran, Maria H.; Habibollah, Saba; Neganova, Irina; Singhapol, Chatchawan; Saretzki, Gabriele; Stojkovic, Miodrag; Armstrong, Lyle; Przyborski, Stefan; Lako, Majlinda
Abstract Fanconi anemia (FA) is a genomic instability disorder caused by mutations in genes involved in replication‐dependant‐repair and removal of DNA cross‐links. Mouse models with targeted deletions of FA genes have been developed; however, none of these exhibit the human bone marrow aplasia. Human embryonic stem cell (hESC) differentiation recapitulates many steps of embryonic hematopoietic development and is a useful model system to investigate the early events of hematopoietic progenitor specification. It is now possible to derive patient‐specific human‐induced pluripotent stem cells (hiPSC); however, this approach has been rather difficult to achieve in FA cells due to a requirement for activation of FA pathway during reprogramming process which can be bypassed either by genetic complementation or reprogramming under hypoxic conditions. In this study, we report that FA‐C patient‐specific hiPSC lines can be derived under normoxic conditions, albeit at much reduced efficiency. These disease‐specific hiPSC lines and hESC with stable knockdown of FANCC display all the in vitro hallmarks of pluripotency. Nevertheless, the disease‐specific hiPSCs show a much higher frequency of chromosomal abnormalities compared to parent fibroblasts and are unable to generate teratoma composed of all three germ layers in vivo, likely due to increased genomic instability. Both FANCC‐deficient hESC and hiPSC lines are capable of undergoing hematopoietic differentiation, but the hematopoietic progenitors display an increased apoptosis in culture and reduced clonogenic potential. Together these data highlight the critical requirement for FA proteins in survival of hematopoietic progenitors, cellular reprogramming, and maintenance of genomic stability. STEM CELLS 2013;31:1022–1029